Different Cytotoxic Effects of Caper from Different Geographical Regions May Be Related to Changes in Mitochondrial Sirt3 - Forouzan Khodaei; Mohsen Rezaei*; Mahmoud Hashemitabar; Marzieh Jafari; Amir Siahpoosh; Mahmood Reza Moein (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Beside its nutritional role, caper (Capparis spinosa) has long been used as an analgesic, anti-inflammatory, anti-diabetic and anti-cancer remedy. In the present study, we tested whether this plant can make effective changes in Sirt3 and mitochondrial function in colorectal carcinoma cell line since mitochondrial dysfunction has long been implicated in both cancer and diabetes and benefit confers by caper in these diseases might be due to mitochondrial alterations. Methods: Total flavonoids and phenolics were assayed using colorimetric tests. Cytotoxicity of a phenolic-flavonoid rich extract of caper collected from two different geographical regions (south and west) were mechanistically studied in HT-29 cell line. Activity of an essential mitochondrial enzyme, Sirt3 has also been evaluated along with other parameters. IC50 of extracts were determined by MTT cytotoxicity assay, cell death and mitochondrial membrane potential were evaluated via flow cytometric analysis. Also, at IC50 concentrations, Sirt3 activity was determined fluorimetrically. Results: The results showed that caper induced significant cytotoxicity in HT-29 cells followed by mitochondrial membrane potential collapse, ROS overproduction, Sirt3 activity alteration and cell death. Conclusions: The above-mentioned cytotoxic parameters were inversely proportional to the phenolic and flavonoid contents of the extract showing that other mechanisms beyond their antioxidant capacities may contribute to their anti-cancer effects. In other term, these results suggest that antioxidant capacity may not directly contribute to the anticancer property.